Transformasi Paradigma PKn Menuju Pengembangan Karakter yang Demokratis dan Partisipatif di Sekolah Dasar - Situmorang, Zenfitri; Ndona, Yakobus; Yunita, Sri; Amri, Khairul (Jurnal Gentala Pendidikan Dasar, 2024)
This research aims to explore the transformation of the Civic Education (PKn) paradigm in elementary schools, as well as identifying the strategies and innovations needed to implement it effectively. This research uses a qualitative approach with a case study design at UPT SPF SDN 101990 Bangun Purba. The results of the research show that there is a transformation of the Civics paradigm in elementary schools, from the old paradigm which focuses on mastering civic knowledge to a new paradigm which emphasizes the development of democratic and participatory citizen character. This transformation is characterized by an emphasis on developing critical thinking skills, problem solving and democratic decision making, as well as developing the character of participatory citizens. This research concludes that there needs to be a change in the implementation of Civics in elementary schools, from the old paradigm which is indoctrinative in nature to a new paradigm which emphasizes the development of civic competence. The implication is the need to increase the understanding and skills of class teachers in Civics learning content, adapt the curriculum and teaching materials, as well as support from schools, parents and the community to create a learning environment that is conducive to the development of civic competence.